A comparative evaluation of dexmedetomidine and magnesium sulfate during awake fiber optic orotracheal intubation in patients scheduled for cervical spine surgeries: A prospective study - Bansal, Ekta; Seema Shende; Shikha Srivastava; Neelima Tandon (Asian Journal of Medical Sciences, 2023)
Background: Fiber optic intubation has become an integral part in management of anticipated difficult airways. Various anesthetic drugs have been used to assist awake fiber optic intubation (AFOI) for producing conscious sedation to provide a calm, cooperative, and responsive patient without respiratory depression for successful awake fibre optic intubation. Aims and Objectives: The aim of the present study was to compare the efficacy of dexmedetomidine and magnesium sulfate during awake fiber optic orotracheal intubation in patients scheduled for cervical spine surgeries. Materials and Methods: A randomized, prospective, and comparative study design was conducted in 60 patients in JAH group of hospitals. All patients were randomly divided into two groups: Group A (n=30) patients received dexmedetomidine (1 μg/kg) and Group B (n=30) patients received magnesium sulfate (40 mg/kg) in 100 ml normal saline over 10 min. The fiber optic orotracheal intubation was performed and primary outcome was level of sedation assessed using Ramsay sedation score. Other parameters of study included cough score and intubation score to compare intubating conditions. The secondary outcomes of study included variations in hemodynamic parameters heart rate, systolic blood pressure, diastolic blood pressure, mean arterial pressure, and SPO2 during drug infusion at 2-min interval, immediately after intubation and every 10 min after intubation till 30 min. Results: Group A (Dexmedetomidine) had better sedation score, cough score, and intubation score with stable hemodynamic variables than Group B (Magnesium Sulphate) with statistically significant results. Conclusion: Patients receiving dexmedetomidine had better sedation providing more optimum conditions for AFOI with stable hemodynamic parameters and lesser adverse effects during the procedure than magnesium sulfate.